Microbial Metabolite Effects on Vasculogenic Mimicry in Metastatic Cancers - Mohammad Kamalabadi Farahani; Aisa Bahar; Hamed Tahmasebi; Valentyn Oksenych; Mojdeh Jahantigh (Cells)
Aggressive cancer cells can form new, functional blood vessel-like structures independently of endothelial cells, known as vasculogenic mimicry (VM), instead of the usual tumor blood vessel formation process. However, the symbiotic relationship between microbial communities and human cells ensures the upkeep of cellular metabolism and the functionality of the immune system and metastatic cancers. This interaction typically happens through the generation and management of hormonal intermediates, metabolites, secondary metabolites, proteins, and toxins. A disturbance in the balance between the host and microbiota can alter the dynamics of their relationship, creating a conducive environment for the development of diseases, such as cancers. This review aims to synthesize the initial evidence on the molecular processes governing the interactions between GM and cancer development and emphasize microbial metabolites’ effects on vasculogenic mimicry. Some microbial metabolites could also contribute to developing interactions between microbes and the tumor microenvironment. While numerous obstacles persist, GM’s immense significance and complete capability in shaping tailored anticancer plans cannot be exaggerated, highlighting the need to investigate a holistic method that includes microbial modulation therapy in cancer management.